Administrative orders and their impact on the teachers of the Iraqi Ministry of Education - Ahmed Abdelkarim, Djassem; Sabeh Chair, Hadher; Ahmed Khedhir, Ahmed (Finance and Business Economies Review, 2020)
The study aims at articulating the relational impact between administrative orders and teachers' performance in Anbar's ministry of education. The study entails the questionnaire as a method of research which includes 25 questions distributed randomly among five schools and (50) teachers. The study concludes that there is a moral and material relationship between the administrative orders and teachers' performance. It also concludes that there is an interrelated relationship of a psychological impact between promotions, bonuses, acknowledgments, and the slow level of responding and viewing the delay of activating the orders that preserve the teachers' rights such annual promotions, bonuses, acknowledgments, and the transformation of teachers from one school to another. The study reaches to positive results concerning the moral relationship between the teachers and the administration of the school which shows a positive collaboration with teachers—a matter that supports and encourages their performance and motivates them to fulfill their responsibilities and works as far as the educational process is concerned